Nove aplikacije v sistemu COBISS - Seljak, Marta (Organizacija znanja, 2007)
The paper presents new COBISS applications and their use by libraries operating within the COBISS.Net network. An emphasis is placed on new featuresin the shared cataloguing system, in particular, when moving t a new COBISS3/Cataloguing interface. Described is a new method of updating bibliographic data which, unlike the existing method, will give preference to the COBIB shared bibliographic database and thus improve the quality and the rationale of the bibliographic system. Based on factual data, the paper also describes the level of use of COBISS3 local applications, and presents news inweb applications to be applied by end users as well as in applications designed to support systems management within the COBISS.Net network.
Keywords: COBISS; COBISS.Net; COBISS3; katalogizacija; podatkovne zbirke; računalniška programska oprema